Catalytic valorization of biomass derived glycerol under methane: Effect of catalyst synthesis method. (15th March 2018) - Austin, Danielle; Wang, Aiguo; He, Peng; Qian, Hui; Zeng, Hongbo; Song, Hua
Highlights: Aromatization of glycerol under methane is technically feasible. Methane presence favors formation of monoaromatics. Catalyst synthesis method has a notable impact on its aromatization performance. Catalytic performance on aromatization is closely related to its physical properties. Abstract: The feasibility of upgrading glycerol using Zn, Cu and Ga modified ZSM-5 was investigated. Different catalyst synthesis techniques were compared for their performance on the aromatization of glycerol under a methane environment at 400 °C and initial pressure of 5 bar. GC–MS analysis showed that the catalyst synthesized using deposition precipitation (DP) resulted in the best performance in terms of the highest yield of monoaromatics in the liquid product when compared with the other synthesis techniques. XRD, NH3 -TPD, Pyridine DRIFT, TEM, CO Chemisorption and XAS were employed to better understand the influencing parameters. High crystallinity, high acidity with a higher proportion of medium acid sites and high metal dispersion were identified as the most important factors influencing aromatization performance. Evidently, the deposition precipitation synthesis technique is effective in obtaining each of these attributes. Additionally, a methane environment increased aromatic production when compared to an inert environment. Methane was found to not only maintain high metal dispersion throughout the reaction, but may participate in the reaction as well. The synthesis technique utilized for the upgrading of glycerol can influence the distribution of products, allowing for increased selectivity of the desired product. The demonstrated feasibility and excellent upgrading performance of the DP synthesized catalyst could make the production of biodiesel more economical and environmentally friendly.